Penerapan Model Project Based Learning Pada Materi Ikatan Kimia Untuk Meningkatkan Hasil Belajar Siswa Kelas X di SMA Negeri 1 Likupang - Andries, Marcella; Krisen, Sofia; Kumajas, Jenny (Chemistry Department, Universitas Negeri Manado, 2024)
This research is classroom action research which aims to improve student learning outcomes in chemical bonding material through the application of the project based learning model. There are several things that underlie this research, namely the low interest in student learning in chemistry subjects which then makes student learning outcomes unsatisfactory. The research carried out is classroom action research (PTK) which takes place in two cycles, in cycle I it is held three meetings and in cycle II it is held two meetings. Each cycle in this research consists of a planning stage. implementation, observation and reflexology Data collection techniques were carried out using observation sheets and written tests. Based on the research results, it was found that the project based learning model could improve student learning outcomes. This can be seen from the percentage of student learning outcomes which increased from 60% in cycle I which then increased to 96% in cycle II.